1980
DOI: 10.1039/c39800000719
|View full text |Cite
|
Sign up to set email alerts
|

Selective formation of propene from CO + H2or C2H4with Fe3(CO)12supported on inorganic oxides. mechanistic implication in Fischer–Tropsch synthesis

Abstract: Sztmmary When a catalyst derived from Fe,(CO),, THE mechanism of carbon-carbon bond formation in Fischer-Tropsch synthesis is not yet clearly understood. Three types of mechanisms are commonly invoked which imply : (i) insertion of CO into a metal-alkyl bond to produce a metal-acyl;l (ii) insertion of a methyl fragment into a supported on magnesia is treated either with CO + H, or C,H, propene is formed selectively; this can be explained on the basis of a carbene + olefin r;r metallacyclobutane mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 0 publications
0
15
0
2
Order By: Relevance
“…In FT active catalysts, for example, it is suggested that bridged carbene is a plausible species to promote olefin homologation [4]. Linear carbene is generally accepted as an important species for olefin metathesis [7].…”
Section: Except For Varying the Reaction Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In FT active catalysts, for example, it is suggested that bridged carbene is a plausible species to promote olefin homologation [4]. Linear carbene is generally accepted as an important species for olefin metathesis [7].…”
Section: Except For Varying the Reaction Temperaturementioning
confidence: 99%
“…Therefore, it has been putatively accepted that the homologation reaction is analogous to olefin metathesis which proceeds via metallacyclic intermediates. In contrast to these, it is suggested that the homologation reaction proceeds via bridged alkylidene and metallacyclic species on iron-based catalyst showing activity for the Fischer-Tropsch (FT) synthesis [4]. These exploratory experimental facts suggest that the active sites for homologation and those for metathesis may require different structural factors.…”
Section: Introductionmentioning
confidence: 97%
“…[17] We have also observed this reaction, with a short lifetime, during Fischer-Tropsch synthesis in the presence of small iron nanoclusters formed by the thermal decomposition of [HFe 3 (CO) 11 ] À /MgO. [18] This reaction has also been reported to proceed with catalysts based on europium or ytterbium deposited on coal in combination with titanium compounds (TiCl 4 , Ti(OiPr) 4 ) [19] as well as with MO x / SiO 2 [20] or Ru/SiO 2 catalysts. [21] However, the catalytic performances of all these systems were either not quantified [17] or proved to be very low [19][20][21] compared to the present W(H) 3 / Al 2 O 3 system.…”
mentioning
confidence: 90%
“…90 min) induction period at 200 8 8Cunless H 2 is added. [218] Other products are methane,1-butene,aswell as cis-and trans-2-butenes.Little is known about the nature of the active site(s) on these Fe-and Mo-based catalysts or the actual mechanism of the ethylene into propylene conversion, and proposed reaction intermediates include metallacarbenes. [218] Other products are methane,1-butene,aswell as cis-and trans-2-butenes.Little is known about the nature of the active site(s) on these Fe-and Mo-based catalysts or the actual mechanism of the ethylene into propylene conversion, and proposed reaction intermediates include metallacarbenes.…”
Section: Direct Homologation Of Ethylene To Propylenementioning
confidence: 99%
“…[217] After decarbonylation, magnesia-supported Fe 3 (CO) 12 also catalyzes the ETP reaction, converting ethylene into propylene at 170 8 8Cw ith 70 %s electivity,a lthough with av ery low conversion (1 %). [218] In the past decade,ETP conversion was also reported on Ni-based mesoporous materials such as MCM-41 [179,219,220] or its aluminum-doped analogue. [218] In the past decade,ETP conversion was also reported on Ni-based mesoporous materials such as MCM-41 [179,219,220] or its aluminum-doped analogue.…”
Section: Direct Homologation Of Ethylene To Propylenementioning
confidence: 99%